Studying additional losses of standard g.652 optical fiber with protective cladding during multiple bending to develop weight control sensor - Alkina, Aliya D.; Mekhtiyev, Ali D.; Neshina, Elena G.; Serikov, Tansaule; Madi, Perizat Sh; Sansyzbay, Kanibek; Yurchenko, Alexey V. (Journal of theoretical and applied information technology)
The article deals with developing an alternative to fiber-optic data transmission lines. One of the problems of telecommunication systems of the Republic of Kazakhstan operation is considered attenuation of signals in FTT data transmission systems. The main idea of using optical fiber of the G.652-656 standard, which is sufficiently sensitive to bends, has been described. Local enterprises have mastered the production of fiber-optic cables and patch cords based on the G.652 standard. Bending causes a loss of the light wave power, changes the phase of propagation of the mode and leads to signal attenuation, in which case users cannot work normally in the Internet. In this article, various types of microbends have been simulated. Microbending of a small radius optical fiber will damage it. This situation arises when the technology of installing a fiber-optic cable is violated. There have been carried out studies aimed at obtaining new scientific results related to the construction of characteristics of additional losses arising from the bending of an optical fiber depending on the number of angles, their degree and the wavelength of optical radiation. Conclusions have been drawn on the further use for the development of sensors based on the control of additional losses during microbending, as well as the development of systems for protecting information transmitted over fiber-optic lines. The studies are aimed at developing software for the numerical calculation of additional losses with an estimate of the accuracy of constructing an approximation according to the given parameters: the number of bends, the angle and wavelength of optical radiation propagating along the fiber core.